Empirical determinants of financial fragility. The case of Colombian firms - De Jesus, Bruno (2025)
Hyman Minsky’s financial instability hypothesis provides a theoretical framework to understand the emergence of endogenous crises in modern economies and how capital flows amplify accumulated imbalances and exacerbate financial constraints in economic units. This inquiry operationalizes the Financial Instability Hypothesis within the Colombian non-listed manufacturing sector through the estimation of discrete-state dynamics and distributional sensitivities. The methodological design constructs two distinct fragility taxonomies to interrogate the determinants of the Hedge, Speculative, and Ponzi classifications. The first specification applies an open-economy cash-flow model derived from Castro (2011), which explicitly internalizes the valuation effects of nominal exchange rate fluctuations on debt service obligations. The second taxonomy, grounded in Nishi (2019), evaluates solvency through the interaction of a flow-based profitability margin and a stock-based liquid asset buffer. To parse the transmission of meso-level economic impulses, the analysis deploys multinomial logit models equipped with a Mundlak correction for correlated random effects alongside recentered influence function regressions. Estimation outputs from the first model confirm that the deterioration of the interest coverage ratio functions as the primary determinant to the Ponzi state, while pre-existing dependence on imported capital acts as a specific transmission channel for currency shocks. The margin-of-safety specification reveals that stock-based liquidity buffers absorb solvency shocks effectively, rendering specific currency exposure variables redundant as predictors of distress. Finally, the dynamic analysis uncovers a temporal asymmetry where contemporaneous sectoral expansions ameliorate immediate default risk through the revenue channel, whereas lagged growth accumulation is associated with the endogenous generation of future fragility. This validates the core thesis of Minsky’s framework: that stability breeds instability.